Peran Manajemen Logistik dalam Meningkatkan Kualitas Pelayanan Kesehatan di Rumah Sakit Umum Sundari - Indah Fadillah; Sumi Fitri Winanti; Wulan Dwi Citra Sari; Putri Adinda Ramadhani Hutagalung; Indah Doanita Hasibuan (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Quality health services are a basic right of the community and it is the responsibility of health institutions to fulfill them. Sundari General Hospital as one of the main health service providers in its area also faces challenges. This study aims to analyze the role of logistics management in improving the quality of health services at Sundari General Hospital. This study uses a qualitative approach that aims to describe the role of logistics management in improving the quality of health services at Sundari General Hospital. The study shows that the distribution of medical logistics at Sundari General Hospital uses a one-stop system with a pharmacy installation as a distribution center for centralized stock control and coordination between units. A flexible logistics management system is implemented with the FIFO and FEFO methods for stock rotation, supported by standard warehouse facilities, thus maintaining the quality and availability of drugs and medical devices for optimal service. Based on the results of the study, logistics management at Sundari General Hospital has been shown to play an important role in improving the quality of health services.